BREASTFEEDING IN THE PERSPECTIVE OF HEALTH AND ISLAMIC RELIGION IN THE EAST JAKARTA REGION - Arini Kusmintarti; Arif Sumantri (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
Exclusive breastfeeding is offering breast milk (ASI) from birth to 6 months old, without any additional water or food. Exclusive breastfeeding in Indonesia is still very low at 37.3%. This is much lower than the target set by the Ministry of Health, which is 80%. Exclusive breastfeeding can prevent stunting in children and in the long term can prevent degenerative diseases. This study aims to explore exclusive breastfeeding in the perspective of health and Islam. The design in this study uses a qualitative study. The main participants in this study were mothers with children aged 2 to 5 years old who lived in East Jakarta and came to the Independent Practice Midwife (TPMB) Endang Irianti. Participants were selected using the purposive sampling method. This research was conducted from March to May 2022. The data was collected through structured in-depth interviews, then the data were analyzed using content analysis. The validity of the data is maintained by using triangulation of data sources. The results showed that almost all participants knew about exclusive breastfeeding and continued breastfeeding until the child was two years old, but all participants knew little about the verses of the Quran that instruct mothers to breastfeed their children and wean them until their children are 2 years old. All participants received support from their husbands, mothers and mothers-in-law to breastfeed exclusively and continue breastfeeding until the child was two years old. Almost all participants breastfed their babies exclusively and weaned their children until the age of two years or more and only a small proportion did not breastfeed exclusively on the grounds that they were pregnant again by the time the child was 3 months old.